Desulfurization of Pyrolytic Fuels by Adsorption and Oxidation (LACCEI, 2024)
Desulfurization is the removal of sulfur or sulfur compounds from hydrocarbons or mixtures of hydrocarbons derived from petroleum, natural gas, or similar fuels. Fuels obtained from the pyrolysis of used lubricating oil, and used tires, have a high content of sulfur compounds, higher than in distilled fuels from crude oil. These sulfur compounds after combustion become SOx, which is a main component of acid rain causing air pollution and environmental degradation. Oxidative desulfurization (DSO) and adsorptive desulfurization (DSA) were performed on a pyrolytic fuel obtained from the pyrolysis of used lubricating oil. The initial sulfur content in the samples varies between 0.12668% and 0.07679% (w/w), in the DSO process up to 9.23% of sulfur was removed under the following conditions: temperature 90°C, reaction time 15 min, H2O2 concentration 3%, and 1.7 g of FeCl3. Then the samples were treated by DSA with silica gel and activated carbon, it was determined that activated carbon is the best adsorbent and removed up to 27.75% of sulfur was. The two treatments (DSO and DSA) were combined in a series arrangement of three activated carbon beds with a height of 15 cm and it was found that up to 92.56% of sulfur can be removed.